Accusations of Islamophobia and Radicalism Against Muslim Women in Hijab in Indonesia: A Bibliometric Analysis - Tamami, Fauziyah; Rahmawati, Siti; Maksum, Muhammad Nur Rochim; Apriantoro, Muhamad Subhi; Muchammad Taufiq Affandi; Shaifurrokhman Mahfudz (Universitas Muhammadiyah Surakarta, 2023)
This study aims to determine the mapping of the development and direction of research on allegations of Islamophobia and Radicalism against Muslim Women wearing hijab in Indonesia using articles indexed by Google Schoolar, WoS, and Scopus databases. This study uses a quantitative approach of bibliometric analysis method to explore all publications indexed in the Scopus database regarding allegations of Islamophobia and radicalism against Muslim women wearing hijab in Indonesia from 2008 to 2023. Data obtained and analyzed using Excel and R/R-Studio. VOSviewer is used to perform visual analysis of keyword occurrence and document citations in a stimulating manner. Researchers found 74 publications that fit the function, subject, and criteria set. The results of this study show an annual growth rate. The papers are analyzed in terms of publications by field of science, the number of studies published annually. The bibliometric analysis performed was limited to Scopus data. Other national and international databases were not taken into account in the study. The limitation of this study is only taking data sets or meta data in publications indexed by Scopus. This study presents a brief overview of the literature accessible to researchers working in the field of Accusations of Islamophobia and Radicalism against Muslim Women and provides recommendations for future research.